Cryptosystem by a community of devices with limited resources. (1st May 2020) - Hadaoui, Rebiha; Tamine, Karim; Daoui, Mehammed; Lalam, Mustapha
Rivest-Shamir-Adleman (RSA) is an encryption algorithm with public-key and is the most widely used for secure data transmission. It provides high safety and consists of modular exponential operation on large numbers. We propose an original approach which makes a distributed calculation of RSA encryption by a community of users endowed with low resources equipment. When a user u of the community wants to encrypte a data X, he exploits the resources of his community. For that, we replace the modular exponentiation operation by a set of calculations dependent of each other and which use fewer resources. These calculations are spread over the members of the user's community to help him perform the operation.